Thermal Stresses in the Wall Connections of Cast Grate Structures - Bajwoluk A.; Gutowski P. (Archives of Foundry Engineering, 2016)
The purpose of this study was to establish a relationship between the type of wall connection used in the cast grates, which are part of the equipment operating in furnaces for heat treatment and thermal-chemical treatment, and stresses generated in these grates during the process of rapid cooling. The places where the grate walls are connected to each other are usually characterized by the thickness larger than the remaining parts of walls. Temperature variations in those places are responsible for the formation of hot spots, and in the hot spots temperature changes much more slowly. The type of wall connection shapes the temperature gradient in the joint cross-section, and hence also the value of thermal stresses generated during cooling. In this study, five different designs of the grates were compared; the difference in them was the type of the designed wall connection. The following design variants were adopted in the studies: X connections with and without holes, T connections with and without technological recesses, and R (ring) connection. Numerical analysis was performed to examine how the distribution of temperature changes in the initial phases of the cooling process. The obtained results served next as a tool in studies of the stress distribution in individual structures. The analysis were carried out by FEM in Midas NFX 2014 software. Based on the results obtained, the conclusions were drawn about the impact of different types of wall connections on the formation of thermal stresses in cast grates.